Oral malignant melanoma: A case report of an unusual clinical and histologic presentation - Uzma Iqbal Belgaumi; Pushparaja Shetty; Shilpa Shirlal (Wolters Kluwer Medknow Publications, 2013)
Malignant melanoma is a potentially aggressive tumor of melanocytic origin. Primary oral malignant melanoma is a rare neoplasm, accounting for 0.5% of all oral malignancies. The present case occurred in a 60-year-old female patient, as a pedunculated growth involving the palate and alveolar ridge and histologically showing a desmoplastic differentiation. The article discusses the distinct clinico-pathologic presentation of this case and emphasizes on the need to identify and report such cases for further understanding of their biologic behavior.